COVID-19 reshaped students’ perceptions of teaching excellence but not their evaluations of teaching - Rayner, Gerard; Papakonstantinou, Theo (Journal of University Teaching and Learning Practice, 2024)
Teaching excellence (TE) at the tertiary level has been extensively researched, with student perceptions of its frequency and the educator attributes that comprise it, increasingly important for student retention and learning, and institutional quality and benchmarking purposes. Despite its myriad of issues, student evaluation of teaching instruments (SETs) are the most commonly used proxies for TE. University students enrolled in medicine, nursing and health science courses were surveyed about TE-associated educator attributes before and after the COVID-19 pandemic. Students were also surveyed about the frequency of TE they experienced, and this was compared with metrics for associated unit SETs. Students’ 2022 perceptions of the frequency of TE were significantly lower than those for 2017, both overall and based on years of university study. Conversely, the mean 2022 SET was significantly higher than that of 2017, indicating a discordance between the perceived frequency of TE and SETs. Applying a framework with validated TE ‘themes’, we found a significant difference between pre- and post-pandemic values for the overall cohorts and non-first year students’ weightings of educator attributes that best describe TE. No such difference was found for first year students. These results strengthen calls for tertiary institutions to develop more authentic TE criteria, bespoke and dynamic SETs that more accurately reflect TE, and relevant educator professional development that will enhance students’ learning gain and overall university experience. The implementation of such initiatives will be increasingly important in a rapidly changing and more disrupted tertiary environment.